Biologically synthesized silver nanoparticles induce neuronal differentiation of SH‐SY5Y cells via modulation of reactive oxygen species, phosphatases, and kinase signaling pathways. Issue 7 (15th May 2014) - Dayem, Ahmed Abdal; Kim, BongWoo; Gurunathan, Sangiliyandi; Choi, Hye Yeon; Yang, Gwangmo; Saha, Subbroto Kumar; Han, Dawoon; Han, Jihae; Kim, Kyeongseok; Kim, Jin‐Hoi; Cho, Ssang‐Goo
Abstract Nano‐scale materials are noted for unique properties, distinct from those of their bulk material equivalents. In this study, we prepared spherical silver nanoparticles (AgNPs) with an average size of about 30 nm and tested their potency to induce neuronal differentiation of SH‐SY5Y cells. Human neuroblastoma SH‐SY5Y cells are considered an ideal in vitro model for studying neurogenesis, as they can be maintained in an undifferentiated state or be induced to differentiate into neuron‐like phenotypes in vitro by several differentiation‐inducing agents. Treatment of SH‐SY5Y cells by biologically synthesized AgNPs led to cell morphological changes and significant increase in neurite length and enhanced the expression of neuronal differentiation markers such as Map‐2, β‐tubulin III, synaptophysin, neurogenin‐1, Gap‐43, and Drd‐2. Furthermore, we observed an increase in generation of intracellular reactive oxygen species (ROS), activation of several kinases such as ERK and AKT, and downregulation of expression of dual‐specificity phosphatases (DUSPs) in AgNPs‐exposed SH‐SY5Y cells. Our results suggest that AgNPs modulate the intracellular signaling pathways, leading to neuronal differentiation, and could be applied as promising nanomaterials for stem cell research and therapy.